1998
DOI: 10.1001/archpsyc.55.1.56
|View full text |Cite
|
Sign up to set email alerts
|

The Risk for Early-Adulthood Anxiety and Depressive Disorders in Adolescents With Anxiety and Depressive Disorders

Abstract: An anxiety or depressive disorder during adolescence confers a strong risk for recurrent anxiety or depressive disorders during early adulthood. Most anxiety and depressive disorders in young adults may be preceded by anxiety or depression in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
976
5
28

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,548 publications
(1,074 citation statements)
references
References 59 publications
65
976
5
28
Order By: Relevance
“…Mental health disorders in childhood and adolescence may predict worse long-term mental health and well-being ( 26,27 ). Longitudinal studies have shown that anxiety or depression during adolescence predict a two-to threefold increase in the risks of developing recurrent anxiety or depression in adulthood ( 41 ). Even subclinical symptoms of depression in adolescence strongly predict major depression disorders in adulthood ( 42 ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Mental health disorders in childhood and adolescence may predict worse long-term mental health and well-being ( 26,27 ). Longitudinal studies have shown that anxiety or depression during adolescence predict a two-to threefold increase in the risks of developing recurrent anxiety or depression in adulthood ( 41 ). Even subclinical symptoms of depression in adolescence strongly predict major depression disorders in adulthood ( 42 ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…A body of work has demonstrated a relationship between anxiety symptoms and disorders and future depression (e.g., Cole, Peeke, Martin, Truglio, & Seroczynski, 1998;Lewinsohn et al 1994;Pine, Cohen, Gurley, Brook, & Ma, 1998). For example, in a 3-year prospective study of a sample of elementary school students, Cole et al (1998) found that the level of anxiety symptoms at one assessment (t i ) were significant predictors of depressive symptoms at followup assessment 6 months later (t i+1 ), even after controlling for the prior level of depression.…”
Section: Preventing Anxiety: the Back Roadmentioning
confidence: 99%
“…Finally, the developmental epidemiology literature has also identified developmental patterns of sequential comorbidity. Symptoms and a diagnosis of anxiety typically precede the development of depressive symptoms or disorder (Avenevoli et al 2001;Cohen et al 1993;Kim-Cohen et al 2003;Pine et al 1998), whereas cognitive theory of depression predict depressive symptoms more specifically compared with anxious arousal symptoms tapping the fear factor, internalizing symptoms characteristic of the broad internalizing dimension, or externalizing behaviors.…”
Section: Introductionmentioning
confidence: 99%